SYSTEM OF WORK ON FORMATION OF STUDENTS' READINESS FOR EDUCATION OF RESPONSIBILITY IN CHILDREN OF SENIOR PRESCHOOL AGE (Pedagogy of Higher and Secondary Education, 2009)
The article covers the modern system of the professional preparation the future tutors of the pre-school establishment to the upbringing responsibility of the person of the under-fives.